Empirical seismic vulnerability, deterministic risk and monetary loss assessment in Fira (Santorini, Greece) - D. Kazantzidou-Firtinidou; Kassaras, I.; A. Ganas (Natural Hazards, 2018)
A deterministic seismic risk and monetary loss model is presented for the capital of Santorini volcanic Island, the town of Fira, on a building block scale. A local seismic source of M5.6 inferred from a recent volcano unrest in 2011–2012, detailed seismic vulnerability of 435 buildings and site conditions deduced from free-field ambient noise measurements were combined toward assessing the EMS-98 damage grade and its probability to occur. The seismic scenario yielded no damage or slight damage for 84{%} of the buildings, 16{%} of the constructions are expected to present moderate-to-heavy damage, while the economic loss amounts to 4 million euros. Although the model predicts low damage and direct economic loss, interaction with the touristic business activities might produce cascade side effects for the economy of the island and consequently Greece's GDP, an important part of which emanates from Santorini.